CORPORATE GOVERNANCE DAN KINERJA KEUANGAN - Supatmi . (Jurnal Bisnis dan Ekonomi, 2007)
The research on the association between corporate governance and financial performances is still inconsistent. The general assumption of the research is that quality of corporate governance is reflected in firms financial performance. This article aims to analyze the association the practice of corporate governance and financial performance among Indonesia firms. The financial performance consists of profitability, liquidity, solvability, activity ratios and Altman z-score. There are 33 firms used as sample in this research. They are firms disclosed in IICG report 2001-2004. Sample of research is the companies that their corporate governance scores have  disclosed by IICG in period 2001-2004. Proxies for profitability, liquidity, solvability and activity are ROE, current ratio, leverage, and total assets to total sales, respectively. The dummy variable to measure bankruptcy firms will be scored if firms have z-score more than 2.65 and 0 otherwise. This research finds that on average sample firms have high score of corporate governance and don’t not face bankruptcy risk. However, score of corporate governance doesn’t impact financial performance. Keywords: Corporate governance, Profitability, Liquidity, Solvability, Activity, Altman